Pengembangan Materi Ajar Teks Cerita Inspiratif Menggunakan Aplikasi Comic Life Di Kelas IX SMP Tahun Ajaran 2022/2023 - Mia Nur’aini Siregar (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
This research is based on the problem that students need varied teaching materials based on interesting comics. So with this problem, the solution is to conduct research on the development of teaching materials for inspirational story texts using the comic life application. This study aims to (1) Know and describe the process of developing teaching material for inspirational story texts using the comic life application, (2) Know and describe the form of teaching material for inspirational story texts using the comic life application, (3) Know the feasibility of teaching material for inspirational story texts using comic life application that has been developed. This development research uses the development model, namely S. Thiagarajan's 4D which consists of define, design, develop, disseminate stages. The results showed that the product results from the development of teaching materials for inspirational story texts using the comic life application in class IX of junior high school were categorized as "Very Eligible" with a percentage result of 85.75%, based on the percentage results from material experts of 83% in the "Very Eligible" category. , media experts 95% in the "Very Eligible" category, Indonesian language teachers 84% ​​in the "Very Eligible" category, and 81% student response in the "Very Eligible" category which concludes that the teaching materials developed are very suitable for use in learning activities .